Machine Learning for Quantum Computing Bridging the Gap between AI and Quantum Algorithms - B. J. Dange, Kaustubh Manikrao Gaikwad, H. E. Khodke, Santosh Gore, S. N. Gunjal, Kalyani Kadam, Sayali Karmode (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This study explains how machine learning techniques are applied to enhance quantum algorithms and examines the interplay between machine learning and quantum computing. It explores quantum data analysis, quantum machine learning, and hybrid quantum-classical techniques, emphasizing their contributions to bridging the gap between artificial intelligence and quantum algorithms. Additionally, it analyzes how quantum data production, quantum-assisted optimization, and quantum neural networks could influence the direction of AI-quantum integration in the future.